2015
DOI: 10.2478/abcsb-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Suspensor Development in Gagea Lutea (L.) Ker Gawl., with Emphasis on the Cytoskeleton

Abstract: The study used fluorescence microscopy to examine changes in cytoskeleton configuration during development of the embryo suspensor in Gagea lutea and to describe them in tandem with the development of the embryo proper. During the early phase of embryo suspensor development, tubulin and actin filaments were observed in the cytoplasm of the basal cell from the micropylar to the chalazal ends of the cell. Around the nucleus of the basal cell were clusters of numerous microtubules. These accumulations of tubulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The cytoskeleton plays an important role in many cellular processes, for example cellular signaling, organelle motility and subcellular compartmentation during plant growth and development [55,56]. To date, only a few studies have been reported on the cytoskeleton during the formation, development and differentiation of polyploid cells of embryo-suspensor in: Sedum acre [23], Alisma plantago-aquatica [57] and Gagea lutea (L.) Ker Gawl., [58]. In all of the above species, the authors have shown the presence of an abundant actin and tubulin cytoskeleton in endopolyploid suspensor basal cells.…”
Section: Suspensor Specializationmentioning
confidence: 93%
“…The cytoskeleton plays an important role in many cellular processes, for example cellular signaling, organelle motility and subcellular compartmentation during plant growth and development [55,56]. To date, only a few studies have been reported on the cytoskeleton during the formation, development and differentiation of polyploid cells of embryo-suspensor in: Sedum acre [23], Alisma plantago-aquatica [57] and Gagea lutea (L.) Ker Gawl., [58]. In all of the above species, the authors have shown the presence of an abundant actin and tubulin cytoskeleton in endopolyploid suspensor basal cells.…”
Section: Suspensor Specializationmentioning
confidence: 93%